Decreased Signs of Nicotine Withdrawal in Mice Null for the β4 Nicotinic Acetylcholine Receptor Subunit - Salas, Ramiro (J Neurosci, 2004)
Withdrawal from chronic exposure to nicotine, the main addictive component of tobacco, produces distinctive symptoms in humans. The appearance of these symptoms is a major deterrent when people try to quit smoking. To study which type of nicotine receptor is relevant for the onset of the withdrawal syndrome, we used a mouse model of nicotine withdrawal. Wild-type mice and mice null for the β4 (β4-/-) or the β2 (β2-/-) nicotinic acetylcholine receptor subunits were implanted with osmotic minipumps delivering 24 mg · kg(-1) · d(-1) nicotine for 13 d. Subsequently, a single intraperitoneal injection of the nicotinic receptor antagonist mecamylamine induced behavioral symptoms of withdrawal measured as increased grooming, chewing, scratching, and shaking, plus the appearance of some unique behaviors such as jumping, leg tremors, and cage scratching. Mecamylamine injection triggered comparable withdrawal signs in wild-type and in β2-/- mice, whereas the β4-/- mice displayed significantly milder somatic symptoms. In addition, nicotine withdrawal produced hyperalgesia in wild-type but not β4-/- mice. Finally, chronic nicotine produced an increase in epibatidine binding in several areas of the brain in both wild-type and in β4-/- mice, but such receptor upregulation did not correlate with the severity of withdrawal signs. Our results demonstrate a major role for β4-containing nicotinic acetylcholine receptors in the appearance of nicotine withdrawal symptoms. In contrast, the β2 subunit does not seem to greatly influence this phenomenon. We also show that the upregulation of epibatidine binding sites attributable to chronic nicotine, an effect associated with β2-containing receptors, is probably not related to the mechanisms underlying withdrawal.